Agricultural outputs and structure adjustments: Empirical evidence based on high-impact weather - Zhai, Zhihong; Jiang, Minxing; Chen, Weixiang; Che, Xiahui (Frontiers in Environmental Science, 2022)
Changes in meteorological conditions affect crop output and planting structure. Based on county-level data of agricultural statistics and weather information in Guangdong province from 1992 to 2018, this paper uses a panel regression model to examine the effects of high impact weather on agricultural outputs and identify the responses in planting structure. The findings show that the rainstorm significantly reduces the per-unit yield (PUY) of rice, and an additional day with daily excessive precipitation (≥50mm) in the growth period leads to an average 0.25% reduction in PUY. However, the vegetable yield is not susceptible to high-impact weather. With a two-period panel regression model and sub-regional climate response analysis, we find that the agricultural planting structure is formed by the regional farming adapting to the high-impact weather (low temperature, high temperature, rainstorms, and high wind). The original rice farmland in the more climate-sensitive areas is transformed into vegetable farming, while the scale of rice is increasing in those less sensitive areas. Finally, we argue that the agricultural sector should assess the impacts of climate change on staple crops and make national climate sensitivity zoning maps. It will provide a scientific justification for making the national agriculture structural adjustment plan.